Investment justification of information technology in manufacturing. (1st January 1999) - Irani, Z.; Ezingeard, J-N.; Grieve, R.J.
The adoption of modern manufacturing technology often requires a large amount of investment, which ultimately needs justification. However, many organisations are increasingly reluctant to pursue capital investments in new technology because it is widely considered that traditional approaches to project justification often overemphasise short-term tangible benefits, and undervalue long-term strategic focuses. The result all too often is indecision. The authors of this paper present a taxonomy of project appraisal techniques, which are used to evaluate manufacturing Information Technology (IT) projects. As the use of IT extends further into the manufacturing domain, there is a growing need to identify a suitable mechanism, which addresses the misalignment between tangible and intangible project implications. As a result, the authors present a conceptual framework, which integrates strategic, tactical, operational and financial dimensions into the investment decision making process.